Targeting Pancreatic Cancer Cells and Stellate Cells Using Designer Nanotherapeutics in vitro - Elechalawar CK; Hossen MN; Shankarappa P; Peer CJ; Figg WD; Robertson JD; Bhattacharya R; Mukherjee P (International Journal of Nanomedicine, 2020)
Chandra Kumar Elechalawar,1 Md Nazir Hossen,1 Priya Shankarappa,2 Cody J Peer,2 William D Figg,2 J David Robertson,3 Resham Bhattacharya,4 Priyabrata Mukherjee1,5 1Department of Pathology, The University of Oklahoma Health Sciences Center, Oklahoma City, OK 73104, USA; 2Clinical Pharmacology Program, National Cancer Institute, Bethesda, MD 20892, USA; 3Department of Chemistry and University of Missouri Research Reactor, University of Missouri, Columbia, MO 65211, USA; 4Department of Obstetrics and Gynecology, The University of Oklahoma Health Sciences Center, Oklahoma City, OK 73104, USA; 5Peggy and Charles Stephenson Cancer Center, The University of Oklahoma Health Sciences Center, Oklahoma City, OK 73104, USACorrespondence: Priyabrata MukherjeeDepartment of Pathology, The University of Oklahoma Health Sciences Center, 975 NE 10th Street, BRC-1409B, Oklahoma City, OK 73104, USATel +1 405-271-1133Fax +1 405-271-2472Email Priyabrata-Mukherjee@ouhsc.eduIntroduction and Objective: Pancreatic cancer (PC) is characterized by a robust desmoplastic environment, which limits the uptake of the standard first-line chemotherapeutic drug gemcitabine. Enhancing gemcitabine delivery to the complex tumor microenvironment (TME) is a major clinical challenge. Molecular crosstalk between pancreatic cancer cells (PCCs) and pancreatic stellate cells (PSCs) plays a critical role in desmoplastic reaction in PCs. Herein, we report the development of a targeted drug delivery system to inhibit the proliferation of PCCs and PSCs in vitro. Using gold nanoparticles as the delivery vehicle, the anti-EGFR antibody cetuximab (C225/C) as a targeting agent, gemcitabine as drug and polyethylene glycol (PEG) as a stealth molecule, we created a series of targeted drug delivery systems.Methods: Fabricated nanoconjugates were characterized by various physicochemical techniques such as UV-Visible spectroscopy, transmission electron microscopy, HPLC and instrumental neutron activation analysis (INAA).Results and Conclusion: Targeted gemcitabine delivery systems containing mPEG-SH having molecular weights of 550 Da or 1000 Da demonstrated superior efficacy in reducing the viability of both PCCs and PSCs as compared to their non-targeted counterparts. EGFR-targeted pathway was further validated by pre-treating cells with C225 followed by determining cellular viability. Taken together, in our current study we have developed a PEGylated targeted nanoconjugate ACG44P1000 that showed enhanced selectivity towards pancreatic cancer cells and pancreatic stellate cells, among others, for gemcitabine delivery. We will investigate the ability of these optimized conjugates to inhibit desmoplasia and tumor growth in vivo in our future studies.Keywords: pancreatic cancer, gold nanoparticles, PEGylation, drug delivery